Gbps Long-Distance Real-Time Visible Light Communications Using a High-Bandwidth GaN-Based Micro-LED - Xiaoyan Liu; Pengfei Tian; Zixian Wei; Suyu Yi; Yuxin Huang; Xiaolin Zhou; Zhi-Jun Qiu; Laigui Hu; Zhilai Fang; Chunxiao Cong; Lirong Zheng; Ran Liu (IEEE Photonics Journal)
In this investigation, we experimentally demonstrated a high-speed Gbps long-distance real-time visible light communication system based on non-return-to-zero on-off keying modulation by using a high-bandwidth Gallium nitride-based micro-LED with a modulation bandwidth of ∼230 MHz and a size of 40 μm $ × $ 40 μm. The maximum real-time data rate obtained is up to 1.3 Gbps at a 3 m free-space transmission distance with a bit-error rate (BER) of 3.4 $ × $ 10 –3 and 1 Gbps at a 10 m distance with a BER of 3.2 $ × $ 10–3, both of which are underneath the forward error correction threshold of 3.8 $ × $ 10–3 required for free-error operation. In addition, when the transmission distance is increased to 16 m in free space through reflecting the emission light beam by blue reflectors mounted on the wall, a data rate of 0.87 Gbps with a BER of 3.5 $ × $ 10–3 is achieved successfully.